Redescription of Ilyarachna zachsi Gurjanova, 1933 (Crustacea:Isopoda: Munnopsidae) from the Sea of Japan, with the synonymisation of I. starokadomskii Gurjanova, 1933 - Golovan, Olga A.; Malyutina, Marina V. (Zootaxa, 2006)
Ilyarachna zachsi Gurjanova, 1933, from the Sea of Japan, is redescribed and I. starokadomskii Gurjanova, 1933 is regarded as a junior subjective synonym of that species. I. zachsi is characterized by the cephalon having a transverse row of 6 dorsal spines, anterior margins of pereonites 1–3 with 4–14 dorsal spines and the male pleopods 2 stylet not reaching the distal end of protopod. The species displays significant intraspecific variability in the armament of pereonites 1– 3. The smaller specimens with 4 long spines are generally males, these having been previously described as I. starokadomskii, while the larger, more spiny specimens are females (the specimen with extreme state of this character was previously described as I. zachsi).